Theory-based intervention module on occupational safety and health (TRIMOSH) in improving knowledge, attitude, and practice among food industry workers: study protocol for a randomised controlled trial - Dapari, Rahmat; Mahfot, Mohd Hafizuddin; Ahmad Zamzuri, Mohd Ammar Ihsan; Md Isa, Zaleha; Hassan, Mohd Rohaizat; Che Dom, Nazri; Syed Abdul Rahim, Syed Sharizman (Public Library of Science, 2024)
Introduction The significant contribution of the food and beverage industry to Malaysia’s Gross Domestic Product is projected to increase in the upcoming years. With the industry’s expansion, the demand for workers on food premises would also continuously increase. The food industry workers are exposed to risks arising from physical, chemical, biological, ergonomic, and psychosocial hazards while performing their duties. Thus, it is essential for these workers to be equipped with proper knowledge, attitude, and practices (KAP) in safety and health. Aims This study aims to develop and evaluate the effectiveness of the safety and health programme TRIMOSH (Theory-Based Intervention Module on Occupational Safety and Health) in improving the knowledge, attitude, and practice among food industry workers. Methods TRIMOSH intervention study is a two-arm randomised, single-blinded, controlled, parallel trial that will be conducted among food industry workers in Selangor, Malaysia. In a partnership with Food Handler Training Schools in Selangor, 10 pairs of Food Handler Training Schools with 12 participants per group (n = 240) will be recruited for balanced randomisation intervention and control conditions. Furthermore, data collection of all participants was conducted at four time points: baseline (T0), immediately (T1), one month (T2), and three months (T3) post-intervention. Generalised Linear Mixed Model (GLMM) will be conducted to determine the effects of intervention within and between study groups. Subsequently, the primary outcomes increase the knowledge, attitude, and practice (KAP) of safety and health at food premises. Clinical Trial Registry registration was approved by the ClinicalTrials.gov committee on October 2022 with the ClinicalTrials.gov Identifier: NCT05571995. This study has also been approved by the Ethics Committee for Research Involving Human Subjects of Universiti Putra Malaysia (JKEUPM-2022-346). All participants are required to provide consent prior to participation. Conclusions The characteristics of the respondents are expected to show no difference between the groups. It is hypothesised that TRIMOSH is effective in improving the knowledge, attitude, and practices of food industry workers in Selangor. The results will be reported and presented in international peer-reviewed journals, conferences, and other platforms. In addition, the TRIMOSH programme will be offered at the national level by the relevant authorities for the benefit of food industry workers.